Komentar terhadap undang-undang badan hukum pendidikan dan kesiapan UNY menjadi badan hukum pendidikan - Anang Priyanto (Jurnal Civics: Media Kajian Kewarganegaraan)
Pro and contra responses arises release of Act of Legal Body of Education (BHP). The emergence of the forementioned Act is mandate of Act of System of National Education. The articles of Act response completelY the objections of the opposing parties against this Act. They should prosecute it through constitutional review in Court of Constitution/ Mahkamah Konstitusi  (MK). They should prove the fundamental weaknesses of its content.  If UNY is reacfy to change its legal body into BHP, whole aspect of its management and conduct should be adjusted to the provisions og the Act. UNY has already tried to anticipate the regulation through preparing the statute of Universiry.